A Case-control Study of Exercise and Kidney Disease: Hemodialysis and Transplantation - Silva-Filho, Antonio; Azoubel, Luana Anaisse; Barroso, Rodrigo França; Carneiro, Erika; Dias-Filho, Carlos Alberto Alves; Ribeiro, Rachel Melo; Garcia, Alessandra Magalhães Campos; Dias, Carlos José; Rodrigues, Bruno; Mostarda, Cristiano Teixeira (International Journal of Sports Medicine, 2019)
We aimed to analyze the effect of an exercise training program in autonomic modulation, and exercise tolerance of hemodialysis and kidney-transplanted patients. 4 groups of exercised and non-exercised patients undergoing hemodialysis and kidney-transplanted subjects had their biochemical tests, and heart rate variability evaluations analyzed. Also, sleep quality, anxiety and depression questionnaires were evaluated. Both exercised groups showed improvements in cardiovascular autonomic modulation, biochemical markers, and exercise tolerance after the exercise training program. The exercised kidney-transplanted patients group showed better improvements in cardiovascular autonomic modulation, biochemical markers, and exercise tolerance when compared to the exercised hemodialysis patients group. Both groups showed improvements in sleep quality, anxiety, and depression. The group of kidney-transplanted patients show better results in the cardiovascular autonomic modulation than subjects undergoing hemodialysis. However, the patients undergoing hemodialysis showed improvements in blood pressure, HDL, hemoglobin and phosphorus, changes not observed in the kidney-transplanted group. Exercise is beneficial for both hemodialysis and kidney-transplanted patients groups. However, exercise programs should be focused mainly in improving cardiovascular risk factors in the HD patients.
Keywords: exercise; chronic kidney disease; kidney replacement therapy; heart rate variability